Projections and the Potential Societal Impact of the Future of Neurotechnologies - Gaudry, Kate S.; Ayaz, Hasan; Bedows, Avery; Celnik, Pablo; Eagleman, David; Grover, Pulkit; Illes, Judy; Rao, Rajesh P. N.; Robinson, Jacob T.; Thyagarajan, Krishnan; , The Working Group on Brain-Interfacing Devices in 2040; Bains, Nena; et al. (Frontiers in Neuroscience, 2021)
Traditionally, recording from and stimulating the brain with high spatial and temporal resolution required invasive means. However, recently, the technical capabilities of less invasive and non-invasive neuro-interfacing technology have been dramatically improving, and laboratories and funders aim to further improve these capabilities. These technologies can facilitate functions such as multi-person communication, mood regulation and memory recall. We consider a potential future where the less invasive technology is in high demand. What this demand matches the current-day demand for a smartphone? Here, we draw upon neuroethics research to predict which particular neuroethics issues may arise in this potential future and what preparatory steps may be taken to address these issues.